2021
DOI: 10.1071/aj20044
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen in Australian natural gas: occurrences, sources and resources

Abstract: Natural or native molecular hydrogen (H2) can be a major component in natural gas, and yet its role in the global energy sector’s usage as a clean energy carrier is not normally considered. Here, we update the scarce reporting of hydrogen in Australian natural gas with new compositional and isotopic analyses of H2 undertaken at Geoscience Australia. The dataset involves ~1000 natural gas samples from 470 wells in both sedimentary and non-sedimentary basins with reservoir rocks ranging in age from the Neoarchea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…The discovery of these hotspots paves the way for detailed studies of noble gas and stable isotopes compositions, but also for careful microbiological and pedological investigations to better constrain H 2 source(s) and migration path. The targeting approach deployed in our study may be applied elsewhere in the world (e.g., Boreham et al., 2021) and more particularly in orogenic belts presenting a geological configuration comparable to the western Pyrenean area. These orogenic areas, rich in ultramafic rocks, could be preferentially targeted for an industrial prospection of native H 2 resources.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of these hotspots paves the way for detailed studies of noble gas and stable isotopes compositions, but also for careful microbiological and pedological investigations to better constrain H 2 source(s) and migration path. The targeting approach deployed in our study may be applied elsewhere in the world (e.g., Boreham et al., 2021) and more particularly in orogenic belts presenting a geological configuration comparable to the western Pyrenean area. These orogenic areas, rich in ultramafic rocks, could be preferentially targeted for an industrial prospection of native H 2 resources.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is mined in BIF-hosted iron ores, mainly in Western Australia, making Australia the first iron ore producer worldwide. The presence of H2 in wells have been noticed in Australia for almost one century [31,32]. More recently, numerous SCD have been noticed in Western and Central Australia, probably indicating H2 seepage [12,26].…”
Section: Australiamentioning
confidence: 99%
“…These rocks are essentially detrital. Nowadays, iron is largely exploited in South Africa, where Fe-rich lithologies are The presence of H 2 in wells have been noticed in Australia for almost one century [31,32]. More recently, numerous SCD have been noticed in Western and Central Australia, probably indicating H 2 seepage [12,26].…”
Section: South Africamentioning
confidence: 99%
“…Hydrogen production will be a major contributor to the decarbonisation of energy, transport and manufacturing industries. Hydrogen from geological sources (geologic hydrogen) has been found in Australian natural gas samples (Boreham et al 2021), gaining an increasing share of exploration investment and activity globally. If found in commercially exploitable quantities, geologic hydrogen could potentially support the transition to a low-carbon economy.…”
Section: Australia's Energy Commodity Resources Basementioning
confidence: 99%
“…If found in commercially exploitable quantities, geologic hydrogen could potentially support the transition to a low-carbon economy. The origins of geologic hydrogen are varied (Boreham et al 2021) and is found in shallow reservoirs encompassing igneous, metamorphic and sedimentary rocks. It is also thought to be a prominent component of the lower mantle-core.…”
Section: Australia's Energy Commodity Resources Basementioning
confidence: 99%